Odpowiedzi

2009-11-14T11:35:01+01:00
A) (1-x)(1+x)(1+x²)=1+x-x-x²(1+x²)=1+x-x-x²+x²=1 .. źle
b) 5y²-3(y+1)(y-1)=5y²-3(y²-y+y-1)=5y²-3y²+3y-3y+3=2y²+3 .. prawidłowo
c) 7(z²-2)-4(z+3)(z-3)= 7z²-14-4(z²-3z+3z-9)=7z²-14-4z²+12z-12z_36=3z²+50.źle
2 3 2
Najlepsza Odpowiedź!
2009-11-14T11:35:12+01:00
A) P = 1 - x^4 = (1-x²)(1+x²) = (1-x)(1+x)(1+x²) = L

b) L = 5y² - 3(y + 1)(y - 1) = 5y² - 3(y²-1) = 5y² - 3y² + 3 = 2y² + 3=P

c) L=7(z² - 2) - 4 (z + 3)(z - 3) = 7z²-14 - 4(z²-9) = 7z²-14-4z²+36= 3z² + 22 = P


wszystkie są tożsamościami
5 2 5